Perancangan Aplikasi Pendataan Reseller Berbasis Android Menggunakan Pemodelan UML (Unified Modelling Language) di Toko Itha Jaya Tas Rantauprapat - Hura, Yarniwati (Journal of Computer Science and Information System(JCoInS), 2023)
Store Itha Jaya Tas is one of the shops that develops business in the field of selling women's bags and already has many resellers who have joined the store. But the reseller registration process is still done manually by recording every reseller data in a book so it is less efficient. To overcome this we need an application that can facilitate the admin in registering a new reseller and facilitate the store owner to see the reseller data that has joined in the store. Reseller registration application is designed and designed using UML (Unified Modeling Language) modeling. The reseller registration application was built using Eclipse and MySQL as a database for data storage. The results of the design of this application in the form of an Android-based reseller registration application that can be used to record every reseller who wants to register.